Adolescentes em conflito com a lei e direitos humanos: rela????es entre medidas socioeducativas e reintegra????o social - Alencar, Ivoneide Pereira de (2017)
The general goal of this research is to analyze the relationships between socioeducational measures of internment and the initial phase of non-school social reintegration of adolescents in conflict with the law applied in a socioeducational internment unit, called CENTRO, for the purposes of this investigation. With respect to the methodology, we used a qualitative approach of exploratory nature and a holistic multiple case study, applying the following data generation techniques: observation, documentary analysis, semi-structured interviews and, for the data analysis, a content analysis based on Bardin???s (2011) framework. We based our understanding on the fact that the reintegration of adolescents in conflict with the law requires a participative and collaborative work between the State and civil society, creating thus a youth protection network. Among the obtained results, the following must be highlighted: a) the coexistence between the internees, the multiprofessional team, the family and society is weakened by the negative force of the infraction; b) the internal routine is based on discipline, a logic that resembles that of prisons; c) non-school education practices do not occur as a process of production of autonomous and emancipated subjects, aiming at training citizens for social reintegration; d) the expectations of adolescent internees are characterized by the belief that ???where there is a will there is a way???, allowing them to cope with the difficulties posed by reality outside the institution; e) the fragility of non-school socioeducational measures in the researched unit is possibly due to the absence of public policies, yielding an ineffective social integration. Finally, the research suggested three aspects to be overcome: 1) the implementation of non-school educational processes, including a preparation for work based on the realities of the current job market; 2) a balance between the socioeducational treatment offered at CENTRO and legal provisions (FC/88 and CYS, 1990) and 3) the development of public and social policies that support families and adolescents seeking to rebuild family ties.